Grey relational analysis of country-level entrepreneurial environment: A study of selected forty-eight countries - Zhu, Rui; Bhutta, Zahra Masood; Zhu, Yong; Ubaidullah, Fizza; Saleem, Madiha; Khalid, Sidra (Frontiers in Environmental Science, 2022)
The aim of the study is to evaluate the entrepreneurial environment of countries and analyze and rank them on the basis of entrepreneurship-related indicators. The study design comprises the review of literature, extraction of secondary data on the phenomenon, and analysis. The research gap has been established through a review of the literature leading toward the development of a problem statement. The cross-sectional data, related to entrepreneurship indicators, is extracted from the website of World Development Indicators WDI (2021) for selected forty-eight countries. Using positivism as a research philosophy and deduction as a research approach, the data are analyzed through Grey Relational Analysis (GRA). On the basis of grey relational grades, the study also classified the countries on the continuum of ‘much better to ‘worse’. The results of the study show that the countries namely the USA, UK, Japan, Australia, Hong Kong, France, and Canada attained the highest grey relational grades and are considered the countries having much better entrepreneurial environments whereas countries namely Poland, Kuwait, Namibia, etc. attained the lowest grey relational grades and are considered the countries having worst entrepreneurial environment. The current research has several practical implications for different economies/countries, entrepreneurial ventures, entrepreneurial aspirants, and researchers as well. On the basis of the findings of the study, the policymakers should refine country-level entrepreneurial policies keeping in view the respective grey relational grades.